SPRZEDAŻ RZECZY KRADZIONEJ - Kacprzak, Agnieszka (Zeszyty Prawnicze, 2017)
THE SALE OF STOLEN GOODS Summary The most complex analysis of the legal consequences resulting fromthe sale of stolen goods can be found in the Digest 18,1,34,3. Paul frames three separate hypotheses, in which the solutions differ depending on whether the contracting parties, or at least one of them, when stipulating the contract, were aware that the goods for sale had been stolen. If both parties were aware that the object of sale was res furtiva, the contract was void, i.e. neither party was obliged towards the other. Where only the buyer was aware of the circumstances then the seler was not bound by the contract. However, only if he voluntarily delivered his performance, could he demand payment. If only party aware that the goods were stolen was the seller, whereas the buyer concluded the contract in good faith, the sale was valid as a whole. This judgement conforms with the opinion of earlier jurisprudence, especially that of Pomponius. The question of what reason underpinned the jurists’ decision on the invalidity of sale, which had res furtiva as an object and was concluded by the parties aware of this fact, appears the first problem to be solved. I would rather dismiss the notion that such a solution could have been based either on the idea of impossibility of performance or on the mere mala fides of the contracting parties. Given that the seller was not bound to transfer ownership to the buyer, the execution of the contract of sale, the object of which was res furtiva, had to be considered possible. Neither does it seem plausible that the invalidity of the contract was provoked merely by the mala fides of the parties. It would be difficult indeed to speak of one party’s bad faith, if there is no good faith to be protected on the other side of the contract. In all probability the objective the jurists had in mind when excluding the validity of a deliberate sale of res furtivae, was to stop the circulation of such goods and render it easier for the owners to recover them. Therefore a deliberate sale of a stolen thing must have been considered invalid on the ground that it tended to violate one of the principles of legal order and hence was contra bonos mores. From the analysis of the three hypotheses considered by Paul results, that the validity of the sale of res furtiva depended on the good faith of the purchaser. Wherever he was unaware that the object of sale had been stolen, the contract was valid, irrespective of the good or bad faith of the seller. On the contrary, if the purchaser was aware, that the object of sale was res furtivay the contract was void in principle. The seller however, if in good faith, was granted the possibility to convalidate it by spontaneous performance. The reason for such a differentiation was probably the fact, that of the two reciprocal performances, which constituted the substance of the contract of sale, only the one, to which the seller was obliged, could violate the legal order and thus was considered defective. Therefor it was precisely the claim of the purchaser, trying to force such an execution in spite of His knowledge of the status of the goods, that was contra bonos mores and hence invalid. In such a situation the seller was not obliged to deliver his performance. Considering the principle of reciprocity of the contract of sale, one must conclude, that the purchaser could not be obliged towards the seller either, and thus, in principle, the whole contract was void. On the other hand, even though the seller could not have been forced to deliver his performance, he did have the possibility to deliver it voluntarily. In such a case, on the basis of the principle of reciprocity, he could claim payment from the purchaser. On this basis the contract became valid.